Risk Sharing in Occupational Pension Programmes Hybrid Plans - Bielawska, Kamila (Studia Oeconomica Posnaniensia, 2017)
The main types of retirement plans, in terms of determining the amount of the expected benefit are defined as benefit plans (DB) and defined contribution (DC) schemes. Their design causes the polarization of risk distribution associated with pension provision. Most of the risks in DB plans are borne by the organizer, while in DC plans by the participant. Hybrid plans offer the possibility of risk-sharing between the stakeholders of a pension plan. Hybrid solutions are gaining in popularity, especially in the context of occupational pension schemes. The aim of the paper is to evaluate the different types of hybrid pension plans in the light of the distribution of the risk associated with providing the expected level of pension.